The Immediate and Sustained Positive Effects of Meditation on Resilience Are Mediated by Changes in the Resting Brain - Kwak, Seoyeon; Lee, Tae Young; Jung, Wi Hoon; Hur, Ji-Won; Bae, Dahye; Hwang, Wu Jeong; Cho, Kang Ik K.; Lim, Kyung-Ok; Kim, So-Yeon; Park, Hye Yoon; Kwon, Jun Soo (Frontiers in Human Neuroscience, 2019)
While recent studies have explored the maintenance of the effect of meditation on stress resilience, the underlying neural mechanisms have not yet been investigated. The present study conducted a highly controlled residential study of a four-day meditation intervention to investigate the brain functional changes and long-term effect of meditation on mindfulness and resilience. Thirty participants in meditation practice and 17 participants in a relaxation retreat (control group) underwent magnetic resonance imaging scans at baseline and post-intervention and completed the Cognitive and Affective Mindfulness Scale (CAMS) and Resilience Quotient Test (RQT) at baseline, post-intervention, and the 3-month follow-up. All participants showed increased CAMS and RQT scores post-intervention, but only the meditation group sustained the enhancement after 3 months. Resting-state functional connectivity (rsFC) between the left rostral anterior cingulate cortex (rACC) and the dorsomedial prefrontal cortex (dmPFC), precuneus, and angular gyrus was significantly increased post-intervention in the meditation group compared with the relaxation group. The changes in rACC-dmPFC rsFC mediated the relationship between the changes in the CAMS and RQT scores and correlated with the changes in the RQT score both immediately and 3-month post-intervention. Our findings suggest that increased rACC-dmPFC rsFC via meditation causes an immediate enhancement in resilience that is sustained. Since resilience is known to be associated with the preventative effect of various psychiatric disorders, the improvement in stress-related neural mechanisms may be beneficial to individuals at high clinical risk.